When Self-Confidence Becomes Social Capital: A Study of Social Interaction Among High School Students - Abid Zahid Fadhillah; Yuda Syahputra; Melina Lestari; Dona Fitri Annisa (Journal of Behavioral Innovation, 2026)
The purpose of this study is to determine the influence of self-confidence on students' social interaction. This study employs a quantitative research design based on positivist philosophy, applied to a specific population or sample. The sampling technique used is generally random, aiming to assess whether self-confidence affects social interaction among 10th-grade students at SMAN 3 Jakarta. The data were analyzed using a simple linear regression coefficient test with the assistance of SPSS. The results showed that self-confidence has a strong positive influence on social interaction, with a t-value of 13.272 and a significance level of 0.000. Statistically, this proves that self-confidence significantly affects students' social interaction.